2020
DOI: 10.3390/cryst10111025
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hierarchically Architectured ZnO for Luminescence, Photocatalytic, Electrocatalytic, and Energy Storage Applications

Abstract: Hierarchically ZnO nanoarchitecture synthesized through coprecipitation technique. Growth process has been analyzed by varying pH from 5.5 to 13 along with post heat treatment process through the observation of surface morphology from 2D plates, triangular, hexagonal rods, needles, and finally to hierarchical. X-ray diffraction (XRD) reveals many intermediate phases along with ZnO which has been eliminated through the proper pH and temperature. The native defects have been discussed by using Raman and positron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…25 Studies reported that a small change in the synthesis parameters, such as pH, temperature, and concentration of the precursors, can effectively result in a variety of morphologies, and ultimately increases the adsorption capacity and dye degradation. [26][27][28][29] Singh et al 30 synthesized the ZnO nanostructures using a co-precipitation technique from pH 5.5 to 13. They reported that the photocatalytic activity of samples increases with an increase in synthesis pH.…”
Section: Introductionmentioning
confidence: 99%
“…25 Studies reported that a small change in the synthesis parameters, such as pH, temperature, and concentration of the precursors, can effectively result in a variety of morphologies, and ultimately increases the adsorption capacity and dye degradation. [26][27][28][29] Singh et al 30 synthesized the ZnO nanostructures using a co-precipitation technique from pH 5.5 to 13. They reported that the photocatalytic activity of samples increases with an increase in synthesis pH.…”
Section: Introductionmentioning
confidence: 99%